Emotional and evaluative models in sports media discourse - G.K. Gimaletdinova; R.R. Kamalova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article considers the phenomenon of emotional evaluation in sports media discourse, with a particular focus on its stylistic features in the English and Italian languages. The topic has received much attention recently due to the growing interest both in sports and in the ways emotional evaluation is expressed in different types of discourse. Our study is based on sports media texts published by 17 English newspapers and 11 Italian periodicals during the 2020 UEFA European Championship. Continuous sampling revealed 1444 cases of emotional evaluation expressed by means of epithets: 720 and 724 units in the English and Italian texts, respectively. A comparative survey of the language units selected as the ones expressing the subjective attitudes of the authors of the newspaper articles was conducted. The textual features of the newspaper articles were examined. The meaning of each unit and its most likely semantic interpretation were determined by the method of semantic analysis. The contextual use of the units was revealed by the method of contrastive stylistic analysis. The obtained results led to a number of generalizations. They demonstrated that epithets are widely used to express emotional evaluations and thus effectively influence interlocutors in sports media discourse. Furthermore, the comparative analysis showed that English and Italian linguistic cultures are generally similar in terms of expressing subjective evaluations, both positive and negative, which could indicate the universality of sports events coverage and commentary. Finally, we found that the models of emotional evaluation typical of sports discourse that are based on the use of epithets can be considered universal categories employed to describe other stylistic devices and tropes as well.